Towards a simple and secure method for binary cryptography via linear algebra (Revista Brasileira de Computação Aplicada, 2017)
A simple and secure binary matrix encryption (BME) method is proposed and formalized on a linear algebra basis. The developed cryptography scheme does not require the idealization of a set of complex procedures or the generation of parallel bit stream for encryption of data, but it only needs to capture binary data sequences from the unprotected digital data, which are transformed into encrypted binary sequences by a cipher matrix. This method can be performed on physical or application layer level, and can be easily applied into any digital storage and telecommunication system. It also has the advantage that the encrypted data length is not increased, which avoids additional burden for data storage and transmission. In order to validate the presented methodology, a GNU Octave program code was written to encrypt and decrypt data files.